Growth and morphological responses of Andrographis paniculate to varying shade and nitrogen fertilization - Khairul Azree Rosli; Siti Aishah Hassan; Mahmud Tengku Muda Mohamed; Johnson Stanslas; Rosmah Murdad; Shahida Mohd Sharif; Izyan Ayuni Mohamad Selamat; Mohammad Mohd Lassim (International Network for Natural Sciences [ INNSpub ], 2018)
Andrographis paniculata (Burm. f.) Nees is a traditional medicinal plant with valuable phytochemical and pharmacological potential. Growth and morphological responses to light and N can be useful measurements to determine favorable growing conditions for A. paniculata. Despite numerous findings on other medicinal and aromatic plants, there is little information about how light and N affect growth and morphology A. paniculata. The objective of this study was to determine the effects of shade and N on growth and morphological responses of A. paniculata. Plants were grown under two shade levels, 0% and 40%, and fertilized with five N rates, 90, 135, 180, 225 and 270kg ha-¹ in a nested design. Shaded plants grew taller with greater total leaf area, specific leaf area, leaf area ratio and net assimilation rate than sun-grown plants. Fertilizing plants with increasing rate of N has increased their height, leaf area index, total leaf area, shoot and root dry mass, leaf mass ratio and root shoot ratio. There was a quadratic relationship between N rate and total dry mass of plants. The goal in commercial A. paniculata cultivation is to produce high yielding high quality plants. Results showed that A. paniculata could adapt to varying levels of shade and N by altering its growth and morphology. Shading at 40% and fertilizing with 225kg N ha-¹ can increase growth and yield of A. paniculata.